Implementation of the Assistance Policy for Building Livable Homes to Improve the Welfare of Low-Income Communities - Diansyah, Eris; Hajar, Siti; Bida, Obed (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This research assistance aims to identify and analyze the implementation of livable housing development policies in improving the welfare of low-income people in Gayo Lues District, Aceh Province, and explore the factors that hinder the performance of these policies. This research was conducted on stakeholders at the Housing and Settlement Area Office of Gayo Lues Regency and the community with a total of 5 (five) research subjects using purposive sampling with the consideration that informants had complete and relevant information by the research objectives. The method used in this research is descriptive with qualitative analysis. Data collection was obtained from interviews, observation, and documentation studies analyzed data using Interactive Model Analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research conducted were tested using Charles O Jones's theory, namely (1) Organizing, (2) Interpretation, and (3) Application. The results of the research analysis show that the Implementation of Livable Housing Development Assistance Policies in Improving the Welfare of Low-Income Communities in Gayo Lues Regency, Aceh Province, has been implemented but has not run optimally because it still faces several obstacles, including from (1). In aspects of community organizing where they do not know the implementing structure, human resources are still minimal in quantity, financial resources in the form of a budget are also still minimal, the community does not know the completeness of the requirements file, and community support is still low in the program, namely only moral support, (2) Aspects interpretation related to socialization that has not been carried out thoroughly to the community, limited assistance and political influence and power in setting priority scales for beneficiaries, and technical instructions that the provisions have not fully implemented, (3) Implementation Aspect regarding the unavailability of standard SOPs, not there is information or explanation from the executor relating to the implementation of the program to the community and there is no definite schedule for the implementation of activities.